Crystal phase engineering of Ru for simultaneous selective photocatalytic oxidations and H2 production. Issue 5 (18th January 2023) - Gebruers, Michaël; Wang, Chunhua; Saha, Rafikul A.; Xie, Yangshan; Aslam, Imran; Sun, Li; Liao, Yuhe; Yang, Xuhui; Chen, Taoran; Yang, Min-Quan; Weng, Bo; Roeffaers, Maarten B. J.
Abstract : The photocatalytic activity of TiO2 in the simultaneous photocatalytic oxidation of organic molecules and H2 production is optimized via crystal phase engineering of Ru cocatalysts. Abstract : Noble metal nanoparticles are often used as cocatalysts to enhance the photocatalytic efficiency. While the effect of cocatalyst nanoparticle size and shape has widely been explored, the effect of the crystal phase is largely overlooked. In this work, we investigate the effect of Ru nanoparticle crystal phase, specifically regular hexagonal close-packed (hcp) and allotropic face-centered cubic (fcc) crystal phases, as cocatalyst decorated onto the surface of TiO2 photocatalysts. As reference photocatalytic reaction the simultaneous photocatalytic production of benzaldehyde (BAD) and H2 from benzyl alcohol was chosen. Both the fcc Ru/TiO2 and hcp Ru/TiO2 composites exhibit enhanced BAD and H2 production rates compared to pristine TiO2 due to the formation of a Schottky barrier promoting the photogenerated charge separation. Moreover, a 1.9-fold photoactivity enhancement of the fcc Ru/TiO2 composite is achieved as compared to the hcp Ru/TiO2 composite, which is attributed to the fact that the fcc Ru NPs are more efficient in facilitating the charge transfer as compared to hcp Ru NPs, thus inhibiting the recombination of electron–hole pairs and enhancing the overall photoactivity.